Citra Wanita Penyihir Dalam Novel Ratna Tribanowati Karya I Made Sugianto: Suatu Kajian Kritik Sastra Feminis - Richa Dwitasari, Ni Luh Kadek; Windhu Sancaya, I Dewa Gede; Suryati, Ni Made (Humanis; Volume 16. No. 1. Juli 2016, 2016)
This study discusses about Ratna Tribanowati Novel with the analysis structure, image of the sorceress, and gender ideology. This study uses the structural theory and literary criticism of feminism. Methods and techniques in this study consisted of three steps: (1) stage of providing data used methods of reading and translation techniques, (2) stage of data analysis used descriptive analytic, (3) stage of presentation of data analysis using informal methods, aided by engineering deductive and inductive. The results obtained in this study are the narrative structure of the novel. Ratna Tribanowati major theme of the novel is love, while the minor theme of this novel is a love story between a man and a woman who finally fused. There are six primary characters important incident in Ratna Tribanowati novel. The character events (major) named Ratna Tribanowati portrayed through the psychological aspect, physical, and sociological. Plot in the Ratna Tribanowati novel follow the usual pattern of tradisional. Setting include the appropriate place and time running storylines. Mandate contained in the Ratna Tribanowati novel is do not be cheap, either not prejudiced, thinking before acting, and the truth will win. Novel image of the sorceress in Ratna Tribanowati is a strong image of religious values is evident. Strong beliefs about religion, Tri Kaya Parisudha appear on this novel. Gender ideology that character novel Ratna Tribanowati about the ideology of feminism is very apparent at the end of the story.